Doubts about mathematical modelling of rapid water filtration - Dąbrowski, Wojciech (Instal, 2023)
Methods of mathematical modelling of rapid water filtration are described, paying particular attention to the divergences in views on the phenomena accompanying the depth filtration of water suspensions. These doubts were described and clarified. It was also described how they were resolved. Although none of the methods proved to be effective in modelling the filtration of coagulated suspensions, and thus did not find direct application to water technology, each of them provided a better understanding of the process to varying degrees.
Keywords: depth filtration; rapid water filtration; physico-chemical models; stochastic models.